2016
DOI: 10.1128/mcb.01019-15
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Cell Growth Factor A Acts via Platelet-Derived Growth Factor Receptor α To Promote Viability of Cells Enduring Hypoxia

Abstract: Vascular endothelial cell growth factor A (VEGF) is a biologically and therapeutically important growth factor because it promotes angiogenesis in response to hypoxia, which underlies a wide variety of both physiological and pathological settings. We report here that both VEGF receptor 2 (VEGFR2)-positive and -negative cells depended on VEGF to endure hypoxia. VEGF enhanced the viability of platelet-derived growth factor receptor ␣ (PDGFR␣)-positive and VEGFR2-negative cells by enabling indirect activation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Notably, VEGF production and neovascularization were strongest in inflamed arteries rich in tissue IFN- γ , suggesting that the strength of aberrant T cell responses regulates VEGF production (17). Thus, besides hypoxia and glucose deficiency, systemic VEGF concentrations may reflect the uncontrolled T cell stimulation occurring in a VEGF-rich host (34, 54, 55). Previous reports have raised the possibility that VEGF can directly inhibit T cell activation (56).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, VEGF production and neovascularization were strongest in inflamed arteries rich in tissue IFN- γ , suggesting that the strength of aberrant T cell responses regulates VEGF production (17). Thus, besides hypoxia and glucose deficiency, systemic VEGF concentrations may reflect the uncontrolled T cell stimulation occurring in a VEGF-rich host (34, 54, 55). Previous reports have raised the possibility that VEGF can directly inhibit T cell activation (56).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, we have shown VEGF-mediated downregulation of PDGFRs (Chen et al, 2015 ), and discovered that both VEGF–PDGFR binding and PDGF–VEGFR binding is high affinity (Mamer et al, 2017 ). Other cross-family studies have identified VEGF–PDGFR binding and signaling (Ball et al, 2007 ; Pennock et al, 2016 ) and VEGFR–PDGFR dimerization in tumor associated pericytes (Greenberg et al, 2008 ). Altogether, these canonical and cross-family RTK mechanisms suggest several possible receptor activation landscapes that can contribute to tumor growth and drug resistance.…”
Section: Roles Of Rtks In Cancermentioning
confidence: 99%
“…RTKs are widely expressed transmembrane proteins (Cadena and Gill, 1992 ; Ferrara et al, 2003 ). Upon ligand binding, they are activated via canonical (Mac Gabhann and Popel, 2007 ; Sarabipour and Hristova, 2016 ) and non-canonical (Steinkamp et al, 2014 ; Chen et al, 2015 ; Pennock et al, 2016 ; Mamer et al, 2017 ) ligand-induced dimerization and tyrosine phosphorylation mechanisms. Importantly, unligated receptors can dimerize (Ruch et al, 2007 ; Chung et al, 2010 ; Low-Nam et al, 2011 ; Lin et al, 2012 ; Comps-Agrar et al, 2015 ; King et al, 2016 ; Sarabipour and Hristova, 2016 ; Sarabipour et al, 2016 ) and signal (Wu et al, 2010 ; Sarabipour et al, 2016 ; Kazlauskas, 2017 ), although ligand binding stabilizes the dimeric receptor structure.…”
Section: Roles Of Rtks In Cancermentioning
confidence: 99%
“…Surprisingly, VEGF also provides immediate benefit to some of the VEGFR-negative cell types. It does so by enabling indirect activation of PDGFRα, which, as mentioned above, promotes survival by lowering the level of p53 [72]. The way that VEGF promotes indirect activation of PDGFRα is by competing with PDGF for binding to PDGFRα [5].…”
Section: Consequences Of Activating the Pdgfrsmentioning
confidence: 99%